The role of self regulation and market mechanisms in tertiary education - Lőrincz, Mónika (Acta Agraria Debreceniensis, 2014)
The social functions of tertiary education have gone through considerable changes with the transformation of economic environment in the more than two past decades. In the decade after the political transformation the number of students in the tertiary education increased more than threefold. Personal interests, social needs and the demands of the society lay different claims to the performance of this sector. The needs for structural transformation of the tertiary education system are connected with the development of social and economic processes. The changes of legal regulations determining the operation of the sector are induced by these factors, which refer to the autonomic characters of the public participants. Tertiary education possesses a specific market environment each of whose characters – both the supply and demand sides – strive for the enforcement of self-regulatory mechanisms.